Finite element analysis of glulaminated timber beam and column / Norhayati Md. Isa - Md. Isa, Norhayati (1997)
The works cover in this project is to determine the flexural strength of glulaminated timber beam and column by using finite element analysis. The analysis consist of determining the maximum displacement of each model, the stress and strain value of the beam , lateral and vertical displacement of column. AH the output values from the analysis are compared with the results obtained from experimental work carried out by the others researches. The solid structure Plane 42 and Beam 3 are used in the finite element analysis of ANSYS software. In this analysis both the timber and glue are specify as layers. Combination from both of this material strength will give the result of displacement when the load are applied to the beam and column. The displacements of the beam found in this analysis are higher relative to the experimental result obtained.